The Roles of Atambua Customs and Challenges in Dealing with Garment Smuggling in Indonesia-Timor Leste Border Area (International Journal of Scientific Research and Management (IJSRM), 2023)
Border areas are often the center of crime and tend to be dominated by issues of transnational crimes, including garment smuggling, mainly used clothes. This study aims to examine the strategy of the Indonesian government in dealing with garment smuggling at the border area between East Nusa Tenggara (NTT) and Timor Leste. The Directorate General of Customs and Excise (DJBC) accordingly exercises its essential role in supervising goods in and out of the border area between Indonesia and other countries. This article discloses that although Atambua Customs and Excise agency has conducted preventive and repressive approaches mainly by carrying out operations, patrols, and surveillance activities at the border area, the used clothes smuggling remains problematic due to officials’ practices of bribery and residents’ permissive actions. The authors use the concepts of transnational crime, garment smuggling, and border security by utilizing a qualitative method with a case study model. Primary data is collected from interviews with the Atambua Customs and Excise agency, and secondary data is collected from documents, books, and websites.